Infant funerary behavior and kinship in Pleistocene hunter-gatherers from Morocco. Issue 135 (October 2019) - Humphrey, Louise; Freyne, Alison; van de Loosdrecht, Marieke; Hogue, Joshua T.; Turner, Elaine; Barton, Nick; Bouzouggar, Abdeljalil
Abstract: Infant remains are relatively uncommon in the late Pleistocene (Upper Palaeolithic) archaeological record. Funerary treatment is considered indicative of social status and mirrors cultural attitudes toward the deceased or the group they represent. Here we report on the burials of six infants, including three who died at birth or shortly thereafter, from Later Stone Age (Iberomaurusian) levels at Grotte des Pigeons, Taforalt, in Morocco dating to ∼14, 500 cal BP. Funerary treatment of the infants was equivalent to that of older individuals within the community, indicating an inclusive social status. The burials of two of the six infants, shown by previous aDNA analysis to be brother and sister, were overlain by ochre stained grinding stones that may have served as grave markers. In this case, a uniquely shared funerary treatment mirrored a close biological relationship, suggesting that kinship contributed to the patterning of funerary behavior within this Pleistocene burial assemblage.